Financial landscape mapping for climate-smart agriculture in the Nyando Basin, Western Kenya - Wattel, Cor; Asseldonk, Marcel van; Wesenbeeck, Lia van; Oostendorp, Remco; Recha, John W.M.; Radeny, Maren A.O.; Gathiaka, John; Mulwa, Richard (2018)
The present case study analyses the financial environment within which the farmers in Nyando operate and within which they deploy their CSA practices. This initial financial mapping will help the project to identify relevant questions to be asked in the financial diaries surveys, including interpretation of the results. It will also be a point of departure for the second phase of the project, when the financial diaries will be discussed with financial institutions in the region to identify the potential of existing financial products and the possible need for new, innovative ones to enable upscaling.